Ecological education in elementary schools. - Eshonqulova Shahnoza Ibodillayevna. (Zien Journals, 2022)
This article provides information on ecological education, a positive attitude toward ecology in elementary schools, improving knowledge of ecology, and preventing environmental pollution.
Keywords: Primary school; lesson process; ecological approaches; ecological training